Mona Lisa smile - Goldsmith-Thomas, Elaine; Schindler, Deborah; Schiff, Paul.; Konner, Lawrence; Rosenthal, Mark D.; Newell, Mike 1942-.; Roberts, Julia 1967-.; Dunst, Kirsten 1982-.; Stiles, Julia 1981-.; Gyllenhaal, Maggie 1977-.; Stevenson, Juliet; West, Dominic 1970-.; et al. ([Culver City, Calif.] Columbia TriStar Home Entertainment, 2004)
Set in 1953, Katherine Watson is a free-spirited graduate of UCLA who accepts a teaching post at Wellesley College, a women-only school where the students are torn between the repressive mores of the time and their longing for intellectual freedom.
Special features: art forum ; college then and now ; what women wanted: 1953 ; music videoo "The heart of every girl" by Elton John ; filmographies ; trailers.
Originally released as a motion picture in 2003.
Director of photography, Anastas Michos ; editor, Mick Audsley ; music, Rachel Portman ; costume designer, Michael Dennison ; production designer, Jane Musky.
Julia Roberts, Kirsten Dunst, Julia Stiles, Maggie Gyllenhaal, Juliet Stevenson, Dominic West, Ginnifer Goodwin, Topher Grace, John Slattery, Marcia Gay Harden
MPAA rating: PG-13, for sexual content and thematic issues.
DVD, region 1, anamorphic widescreen; Dolby digital 5.1 (English, Dolby digital 2.0 (French) .
Keywords: Wellesley College -- Drama; Women college students -- Drama; Women college teachers -- Drama; Feminism -- Drama; United States -- History -- 1953-1961 -- Drama; Feature films -- United States; Films for the hearing impaired